THEOMORPHY METAPHORS - Maxsetbayevna, Kunnazarova Sholpanay (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigates the nature and functions of theomorphic metaphors in Karakalpak folk tales, focusing on their linguistic, linguocultural, and linguocognitive features. It aims to explore how these metaphors reflect the national outlook, cultural connotations, and anthropocentric worldview of the Karakalpak people. Method: The research employs a qualitative analysis of metaphorical expressions in Karakalpak folk tales, examining their linguistic structure, cultural significance, and cognitive underpinnings. It integrates a comparative approach, linking the metaphors to broader metaphorological theories and identifying their unique contributions to linguistic anthropology. Results: The findings reveal that theomorphic metaphors such as mástan mama, dáw, peri, ájiyne, jin, albasly, and Kydyr convey profound insights into human nature and societal values. These metaphors go beyond literal meanings, serving as a medium to articulate deep cultural and spiritual concepts preserved in oral traditions. Novelty: This research highlights the pivotal role of theomorphic metaphors in representing the worldview of the Karakalpak people, offering a new perspective on the interplay between language, culture, and cognition in folklore. It enriches metaphorology by emphasizing the unique cultural dimensions of metaphors in Karakalpak folk tales.